Simultaneous effects of water and nitrogen stress on the vegetative and yield parameters of choy sum (Brassica chinensis var. parachinensis) - Kamarudin, Khairun Nisa; Teh, Christopher Boon Sung; Jaafar, Hawa Z. E. (Universiti Putra Malaysia Press, 2016)
Hypothetically, leafy vegetables need water and nitrogen (N) simultaneously in their applications for good growth. Therefore, this study was conducted to determine the effects of four watering frequencies (watering once a day, once a week and once in every two weeks and no watering) and five levels of nitrogen (0, 34, 68, 136 and 272 kg N ha-1) on the vegetative and yield parameters of choy sum over a period of four weeks. The choy sum was grown in polyethylene bags under a rain shelter. The experimental design was a split-split plot with four replications. Plant vegetative and yield parameters measured weekly were plant height, leaf number, total leaf area, maximum root length, the various plant part weights and total tissue nitrogen. Water stress detrimentally affected choy sumfs leaf growth more than root growth and the effect of water stress was more than nitrogen stress. Higher nitrogen rates in water-stressed condition increasingly reduced the number of leaves and height of the choy sum. Choy sum grown under once-a-day watering and once-a-week treatments did not experience water stress. The optimal soil water content and nitrogen application rate were 0.4 m3 m-3 and 30 to 40 kg N ha-1, respectively. The rate of 34 kg N ha-1 and once-a-week watering treatment generally gave the highest values for all the measured vegetative and yield parameters. Under lower and point of sufficient nitrogen rates, nitrogen was used for leaf thickness and weight rather than for intercepting light via leaf area expansion.